Analysis of tensile strength and microstructure on GTAW- Aluminum 6061 welding results - Ardani Ahsanul Fakhri; Basyirun Basyirun; Ahmad Fikrie; Prihatno Kusdiyarto (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
The process of joining aluminum metal requires a special welding method. The use of GTAW welding is a suitable method for joining aluminum plates. This research is intended to analyze the tensile strength and microstructure of the GTAW Aluminum 6061 welding with various currents. The research method used in this research is experimental research. Welding current variations used in this study were 100A, 115A, and 130A, then tested using a destructive test, tensile test. The data analysis used in this study is descriptive analysis, where the data obtained are averaged and then described and concluded. The results of microstructure research on GTAW welding show that changes in the microstructure are very visible in the HAZ area and the weld metal, the greater the heat input, the more spread the Mg2Si grains will be. Good structural dispersion only occurs at 130A current. This is different from the base metal which does not change the material structure at all. Based on the tensile test, the tensile stress value is 80.9 MPa at 100 A current, 84.9 MPa at 115A current variation, and the highest tensile strength is 86.7 MPa at 130A current. So, it can be concluded that the higher the current used, the better the microstructure and tensile strength produced.